Electroanalysis of ascorbic acid: A comparative study of laser ablation voltammetry and sonovoltammetry - Akkermans, R; Wu, M; Bain, C; Fidel-Suarez, M; Compton, R (1998)
The electroanalytical detection of L-ascorbic acid via its two electron oxidation in aqueous solution is the subject of a comparison of two voltammetric methodologies both of which rely in part on electrode abrasion. First in sonovoltammetry cavitational collapse at the electrode-solution interface can lead to electrode erosion and activation. Second in laser ablation voltammetry (LAV) a 10 Hz pulsed laser (532 nm, 0.7 mJ per pulse) is used to abrade the electrode. In both cases the concomitant agitation of the solution leads to regular refreshment of the diffusion layer so that at sufficiently extreme potentials sustained currents (transport limited currents) are observed which scale with the concentration of ascorbic acid present and permit quantitative electroanalysis. Comparison of the methods as applied to ascorbic acid shows that for LAV the laser light intensity can be adjusted for maximum ablation of surface adsorbed blocking species but with minimum damage to the platinum surface itself. In contrast the sonovoltammetry technique does not facilitate selective erosion of surface adsorbed species. Instead the mass transport, amount of cavitation and damage to the electrode are all interlinked with the intensity of ultrasound employed. Thus while the amount of cavitation at the electrode surface can be controlled the relative adsorbate/electrode abrasion cannot. The limiting currents under insonation were found to be substantially (ca. 15 times) larger than for LAV suggesting that the major benefit of sonovoltammetry is in terms of enhanced mass transport whereas LAV shows more selective cleaning activation. The development of a novel sono-LAV is therefore reported which retains the merits of both the separate experiments in isolation. Thus the cleaning potential of LAV is coupled with the mass transport enhancement of ultrasound. Application to the quantitative electroanalysis of ascorbic acid is reported.